Endoparasites of Enyalius bibronii Boulenger, 1885 (Squamata: Leiosauridae) in the Semi-arid Caatinga of northeastern Brazil - Samuel Cardozo Ribeiro (2025)
Studies on parasites are essential tools for understanding the ecological dynamics of variations in population abundance, structural changes in communities, and the coevolutionary processes of their hosts. They play a fundamental role in modulating biodiversity and serve as excellent models for studying host-parasite relationships. In this context, we used samples collected in species surveys in four protected areas to describe the endoparasite communities of Enyalius bibroniiBoulenger, 1885 (Squamata: Leiosauridae) in the Caatinga domain of northeastern Brazil and investigated the factors that influence the composition of these communities. We analyzed 166 specimens of E. bibronii. The composition of endoparasites varied between sampling sites, but we identified six parasitic species, with Physaloptera lutzi Cristófaro, Guimaraes & Rodrigues, 1976 and Parapharyngodon alvarengai Freitas, 1957 present in three of these sites. The relation between host size and parasite abundance was significant in some areas, while in others it was not. The parasite community described indicates relatively low diversity. However, our data present several new parasite records infecting E. bibronii. We highlight the unique parasite composition in each area, emphasizing the need for future studies to evaluate parasite distribution comprehensively.